2019
DOI: 10.21475/ajcs.19.13.10.p1996
|View full text |Cite
|
Sign up to set email alerts
|

Spray volume deposits and fungicide efficacy on soybean rust (Phakopsora pachyrhizi)

Abstract: Soybean rust (SBR), caused by Phakopsora pachyrhizi, is one of the most destructive fungal diseases affecting soybean yields in many countries. Fungicide application methods that provide better SBR control efficacy may reduce soybean losses due to this disease. We investigated the effects of spray volumes applying the fungicide pyraclostrobin plus epoxiconazol at 133 + 50 g a.i. ha-1 by a conventional sprayer (CS) and an air-assisted sprayer (AAS). Field experiments were conducted comparing the effects of spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For both bee species, there was a tendency for greater contamination when they were on the upper parts of the plants, especially for cotton plants. This greater contamination of bees positioned on the top of the plants is due to more product hitting these leaves, as observed by Prado et al (2019), who found higher levels of deposition on the upper leaves of soybean plants (69%), followed by the middle (22%) and lower (9%) parts, in controlled spray assays. The spraying equipment they used was similar to what we used in our study.…”
Section: Beesmentioning
confidence: 56%
“…For both bee species, there was a tendency for greater contamination when they were on the upper parts of the plants, especially for cotton plants. This greater contamination of bees positioned on the top of the plants is due to more product hitting these leaves, as observed by Prado et al (2019), who found higher levels of deposition on the upper leaves of soybean plants (69%), followed by the middle (22%) and lower (9%) parts, in controlled spray assays. The spraying equipment they used was similar to what we used in our study.…”
Section: Beesmentioning
confidence: 56%